IDENTIFICATION OF GROWTH CENTERS AND HINTERLAND AREAS THROUGH SCALOGRAM, GRAVITY, KONIG AND SHIMBEL VALUE APPROACHES IN LABUHANBATU SELATAN DISTRICT 2021 - Panggabean, Nurhanisra; Nurwihastuti, Dwi Wahyuni (Jurnal Samudra Geografi, 2025)
To speed up and simplify development in an area, it is important to identify areas that have the potential to become growth centers. The more developed the growth center, the more advanced the supporting areas or hinterlands will be. This research aims to analyze sub-districts which are centers of growth and hinterland areas in South Labuhanbatu Regency. This analysis can be carried out using the scalogram method, gravity, and Konig and Shimbel values. The research results show that Kotapinang sub-district is the center of growth, while Sungai Kanan, Silangkitang, Kampung Rakyat and Torgamba sub-districts act as hinterland areas.